Reconstructing prehistoric demography: What role for extant hunter‐gatherers?. Issue 6 (26th October 2020) - Page, Abigail E.; French, Jennifer C.
Abstract: Demography is central to biological, behavioral, and cultural evolution. Knowledge of the demography of prehistoric populations of both Homo sapiens and earlier members of the genus Homo is, therefore, key to the study of human evolution. Unfortunately, demographic processes (fertility, mortality, migration) leave little mark on the archeological and paleoanthropological records. One common solution to this issue is the application of demographic data from extant hunter‐gatherers to prehistory. With the aim of strengthening this line of enquiry, here we outline some pitfalls and their interpretative implications. In doing so, we provide recommendations about the application of hunter‐gatherer data to the study of demographic trends throughout human evolution. We use published demographic data from extant hunter‐gatherers to show that it is the diversity seen among extant hunter‐gatherers—both intra‐ and inter‐population variability—that is most relevant and useful for understanding past hunter‐gatherer demography.